Long term performance after merger & acquisition sectors in Malaysia / Nur Syafiqah Mohd Said - Mohd Said, Nur Syafiqah (Faculty of Business Management, 2017)
This study is to investigate the long term performance of merged companies in Malaysia according to its sectors. In this studies, 58 merged companies in 2010 were selected. The performance of companies were measured using abnormal return for three years from the merger date. The Cumulative Abnormal Return were used as a tools of measurement. This study also will tell us whether the decisions of after merger will give high performance to the companies as compared to the market. T values is using as to test the hypothesis whether the M&A will influence the performance or not.